Дослідження кібербезпеки технології Інтернету речей (IoT) з використанням хмарних обчислень - Ларабі Фоуад (My University, 2023)
The object of research is the processes of functioning of IoT telecommunication systems using cloud computing. The subject of the research is the characteristics of IoT telecommunication systems using cloud computing. The purpose of the work is to analyze the architecture and technology parameters of IoT telecommunication systems using cloud computing, as well as to improve the methods of information protection of such systems. Research methods – empirical analysis, comparison, analytical modeling. Today, the topic of introducing a new generation of IoT networks using cloud computing is relevant, as nowadays there is a substantial increase in the number of users and information flows in IoT networks. The paper analyzes modern IoT networks using Fog Computing and Cloud Computing technologies. It is proposed to improve the method of information protection of IoT systems. The probability of threat reflection in the IoT system has been calculated. Recommendations for increasing the protection of IoT systems have been developed.
Keywords: IoT; Fog Computing; cloud computing; multi-level protection; Threats; Vulnerabilities